Clinical evaluation of DMARDs and NSAIDs in cases of Rheumatoid arthritis in Chhattisgarh - Maheshwari, Basant Kumar; Khodiar, Prafulla Kumar; Rath, Debapriya (Asian Journal of Medical Sciences, 2018)
Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by polyarticular inflammation with systemic symptoms like malaise, fatigue and fever. Various groups of drugs have been used along with supportive therapies (physical and occupational) for the treatment of rheumatoid arthritis. Non-steroidal anti-inflammatory drugs (NSAIDs) and disease modifying agents in rheumatoid disease (DMARDs) are the two major classes among them. However, none of these medications have proved to be successful enough to be accepted universally as the standard therapy for RA. Aims and Objective: To compare the clinical efficacy of nimesulide as a standalone therapy with combination therapy of nimesulide plus methotrexate and nimesulide plus hydroxychloroquine. Materials and Methods: The study comprised of three groups of rheumatoid arthritis patients. Each group consists of 32 study subjects. Group 1, 2 and 3 consisted of patients taking nimesulide alone, nimesulide plus hydroxycholoroquine and nimesulide plus methotrexate respectively for the disease. The cases were followed up to a period of six months and based upon subjective & objective (Radiological and serological examination) criteria, results have been evaluated. Results: Observations have revealed that nimesulide plus hydroxycholoroquine combination produced significant improvement in the patients in mild, moderate and severe cases of rheumatoid arthritis as compared to nimesulide plus methotrexate. The improvement observed was least in the patients who received nimesulide as standalone therapy. No significant adverse drug reaction was seen in any of the study groups. Conclusion: The study concludes that nimesulide plus hydroxychloroquine combination can be used in cases of rheumatoid arthritis as disease modifying drugs without noticeable toxicity in doses used in this study in patients who have no renal and hepatic insufficiency. Asian Journal of Medical Sciences Vol.9(1) 2018 61-64